ANALISIS SISTEM AKUNTANSI PENERIMAAN KAS DAN PENGELUARAN KAS DALAM UPAYA PENINGKATAN EFEKTIVITAS PENGENDALIAN INTERNAL: Studi pada Koslo Hotel Yogyakarta - Maria Margaretha Tifany Lebasue; Manendha Maganitri Kundala; Hasanah Setyowati (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2023)
The research entitled Analysis of Cash Receipts and Cash Disbursement Accounting Systems in Efforts to Increase the Effectiveness of Internal Cont rol (Study at Koslo Hotel Yogyakarta) aims to analyze how internal cash control is implemented at Koslo Hotel Yogyakarta and compared with cash accounting system theory and internal control theory. This study examines the elements related to the cash receipts and cash disbursement system starting from the documents used, related functions, accounting records and procedures carried out and analyzes how effective the internal controls are implemented. This study also aims to formulate what efforts can be made to improve internal control that has been implemented. Data collection techniques used were interviews, observation and documentation with qualitative research methods and presented descriptively. From the results of the study it can be concluded that Koslo Hotel Yogyakarta has not fully implemented the elements in internal control such as separation of functions and authority because there are still multiple functions by one part. Koslo Hotel Yogyakarta also has not carried out practices and documents that are in accordance with cash system theory but Koslo Hotel Yogyakarta efforts in carrying out internal checks are considered capable of reducing the risk of irregularities.